2014
DOI: 10.1128/jvi.01000-14
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid in EBNA-2 Determines Superior B Lymphoblastoid Cell Line Growth Maintenance by Epstein-Barr Virus Type 1 EBNA-2

Abstract: Sequence differences in the EBNA-2 protein mediate the superior ability of type 1 Epstein-Barr virus (EBV) to transform human B cells into lymphoblastoid cell lines compared to that of type 2 EBV. Here we show that changing a single amino acid (S442D) from serine in type 2 EBNA-2 to the aspartate found in type 1 EBNA-2 confers a type 1 growth phenotype in a lymphoblastoid cell line growth maintenance assay. This amino acid lies in the transactivation domain of EBNA-2, and the S442D change increases activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 33 publications
(42 reference statements)
7
53
0
Order By: Relevance
“…Thus, gene repression due to binding at EBNA3-only sites may still be attributable to impaired (abrogated) EBNA2 binding. This phenomenon may explain the recent discovery that the increased transforming effects of EBNA2 from type I EBV compared to that from type II EBV are due to increased binding of EBNA2 at ETS/IRF4 sites (12). The "novel" binding sites observed with type I EBNA2 may actually be due to an enhanced ability to compete with EBNA3C for binding at ETS/IRF4 sites.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Thus, gene repression due to binding at EBNA3-only sites may still be attributable to impaired (abrogated) EBNA2 binding. This phenomenon may explain the recent discovery that the increased transforming effects of EBNA2 from type I EBV compared to that from type II EBV are due to increased binding of EBNA2 at ETS/IRF4 sites (12). The "novel" binding sites observed with type I EBNA2 may actually be due to an enhanced ability to compete with EBNA3C for binding at ETS/IRF4 sites.…”
Section: Discussionmentioning
confidence: 78%
“…EBNA2 upregulates the other EBV latent gene products, as well as cell oncogenes, such as c-myc, required for LCL growth (5)(6)(7)(8). EBNA2 effects are substantially similar, but not identical, to those of ICN (9)(10)(11)(12). Unlike that of ICN, EBNA2 activation is constitutive and ligand independent.…”
Section: Epstein-barr Virus (Ebv) Latent Gene Products Cause Human Camentioning
confidence: 73%
See 1 more Smart Citation
“…The polymorphisms we found in the EBNA2 gene may have functional consequences as supported by recent data showing that a single amino acid in EBNA2 determines superior B lymphoblastoid cell line growth maintenance. 29 The allelic variants we described may affect the host-virus interplay at different levels: (1) the same region is involved in interactions with cellular proteins such as Nur77 30 and SMARCB1 31 that have been associated with MS susceptibility 32 and antiviral responses 33 ; (2) the gene region we investigated is important for successful strategies of EBV immune evasion 34,35 ; (3) last, but not least, the EBNA2 messenger RNA, where we found MS-related variants, belongs to the targetome of human micro-RNAs that may serve to keep in check EBV infection. 36 MS may resemble other immune-mediated diseases in which infectious agents are thought to have a key role.…”
mentioning
confidence: 99%
“…More detailed analysis showed that converting a single amino acid of type 2 EBNA2 from serine to the aspartate found in type 1 EBNA2 (S442D) was sufficient to give the type 1 growth maintenance of LCLs (Tzellos et al 2014). That amino acid is in the transactivation domain (TAD) of EBNA2, and the TAD of type 1 EBNA2 was about 2-fold more active in a standard TAD reporter assay.…”
Section: Functional Difference Between Type 1 and Type 2 Ebna2mentioning
confidence: 98%